CLONING OF A TRYPSIN-LIKE SERINE PROTEASE AND EXPRESSION PATTERNS DURING PLASMODIUM FALCIPARUM INVASION IN THE MOSQUITO, ANOPHELES DIRUS (PEYTON AND HARRISON) - Sriwichai P. (2014)
Understanding specific gene regulation during responses to malaria infection is key to dissecting the mosquito defense mechanisms and host/parasite interactions. A full-length serine protease cDNA was isolated from the fat body of female Anopheles dirus, a major malaria vector in Thailand. The predicted amino acid sequence of SERF4 identifies it as a member of the serine protease family containing a single trypsin-like protease domain. Digestive trypsins function in the female mosquito midgut and are inducible in two phases in this tissue upon blood intake. However, the gene was highly upregulated in the midgut at day 3 postinfection by Plasmodium falciparum. In situ hybridization confirmed that SERF4 transcripts were located in the midgut epithelial cells rather than hemocytes or other tissues associated with the midgut. SERF4 was also strongly downregulated in the whole insects at day 16 after infection in comparison with the blood-fed control. Changes in the expression of the SERF4 gene in response to infection with this human malaria parasite suggest a role in parasite-specific innate immunity. © 2012 Wiley Periodicals, Inc.